2019
DOI: 10.1021/acs.chemmater.9b04138
|View full text |Cite
|
Sign up to set email alerts
|

Stabilizer-Free CuIr Alloy Nanoparticle Catalysts

Abstract: We present the direct synthesis of stabilizer-free Cu–Ir alloy nanoparticles (NPs) with tunable compositions. Cu and Ir are classically immiscible in the bulk. Therefore, the physical and catalytic properties of Cu–Ir alloys are largely unknown. A convenient microwave-assisted method utilizes readily available Cu2+ salts and IrCl3 in a modified polyol reaction; NaOH facilitates rapid solvent-assisted coreduction to yield Cu x Ir(100–x)NPs, where x can be varied within the approximate range 10–50. The as-synthe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 72 publications
0
25
0
Order By: Relevance
“…Further, 2D energy-dispersive spectroscopy (EDS) mapping of the NPs showed a homogeneous distribution of Cu and Ir across the NPs. 37 The actual composition of the as-synthesized alloy NPs was found to be close to the nominal ratio, as indicated by inductively coupled plasma optical emission spectroscopy of bulk samples (ICP-OES) (Table S1). Corresponding TEM images showed that the alloy NPs have an average size of around 2 nm, similar to the monometallic IrNPs (Figure S5).…”
mentioning
confidence: 53%
See 2 more Smart Citations
“…Further, 2D energy-dispersive spectroscopy (EDS) mapping of the NPs showed a homogeneous distribution of Cu and Ir across the NPs. 37 The actual composition of the as-synthesized alloy NPs was found to be close to the nominal ratio, as indicated by inductively coupled plasma optical emission spectroscopy of bulk samples (ICP-OES) (Table S1). Corresponding TEM images showed that the alloy NPs have an average size of around 2 nm, similar to the monometallic IrNPs (Figure S5).…”
mentioning
confidence: 53%
“…35,36 Here, bimetallic Cu x Ir (100−x) NPs with various target compositions (x = 10, 25, and 50) were prepared using our previously developed methods. 37 The alloy Cu x Ir (100−x) NPs were deposited on a-SiO 2 , and their catalytic activities for nitrite reduction were measured. Powder X-ray diffraction (PXRD) patterns confirmed the random solid-solution structure of the alloy NPs, as the reflections showed a consistent shift to a higher angle with an increasing Cu content (Figure 3a).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Among the most used photocatalyst are the nanostructured metal oxides [10,11]. However, their current preparation involves mainly in-solution methods [147][148][149][150][151][152][153][154], which present some problems in the isolation of the solid by elimination of the solvent as well as the elimination of the template and of the stabilizer [151].…”
Section: Photocatalytic Applicationsmentioning
confidence: 99%
“…57,78 Ten randomly alloyed Pd 75 Ag 25 (111) surfaces were generated using our Python code based on the Atomic Simulation Environment library. 79 Since our μwI-assisted synthesis process was kinetically controlled, 80,81 the binding site sampling from a sufficient amount of randomly generated surfaces was found to be more representative than the calculations on ordered alloy structures. 82 Each average N or N 2 binding energy was sampled from ten binding sites on these surfaces.…”
Section: Acs Catalysismentioning
confidence: 99%